THE CONSTRAINTS OF MANAGEMENT OF ZAKAT AND ITS POTENTIALS IN POVERTY REDUCTION (Case Study Medan City) - Mujiatun, Siti (Advances in Social Sciences Research Journal, 2018)
This study aims to reveal the potential of zakat that has not been managed optimally, especially in the city of Medan. The government such as issuing laws on the management of zakat and establishing a formal institution in order to collect and channel zakat society has made various efforts more efficiently. Currently management efforts, especially zakat profession has shown results in reducing poverty even though not optimal. Various obstacles still exist so that necessary evaluation and strategic steps for the management of zakat to be better in the future.